HISTOLOGICAL CHANGES IN PARTS OF FOREGUT OF RAT AFTER INDOMETHACIN ADMINISTRATION - Ilahi, Maqbool; Khan, Jehanzeb; Inayat, Qaiser; Abidi, Tuqqaya Sultana (Journal of Ayub Medical College Abbottabad, 2006)
Background: Indomethacin, a non-steriodalanti-inflammatory drug, is used mainly for the treatment of painful joints such as rehumatoid arthritis, osteo-arhtritis, gout, ankylosing spondylitis etc. It relieves pain, reduces swelling and tenderness of the joints. It also induces ulceration of stomach and small intestine both in experimental animals and humans. Material and Methods: In this study indomethacin was given intrapertioneally in maximum therapeutic dose (4 mg/Kg body weight) to three experimental groups B, C and D for one, two and three weeks respectively. Group A was the control group. Results: Effects were observed in stomach pylorus and proximal duodenum. In the stomach pylorus, well defined superficial ulcers were identified during initial two weeks of drug administration. The ulcer penetrated as for as muscularis mucosae and ulcer bed had coagulative necrosis and inflammatory cells. During third week, stomach pylorus showed minor damage in the form of focal necrosis. Duodenum was affected less than stomach and showed villi with lost tips, tilted and distorted villi. Morphometric analysis showed changes in stomach pylorus and in duodenum. The number of mitotic figure was significantly increased in stomach pylorus. Duodenum showed insignificant to significant decrease in the height of villi. Increase in the number of goblet cells, columnar cells, and mitotic figure was also noted; which was undoubtedly part of the tissue response to an injury. Conclusion: These observations suggested that indomethacin given in a ma ximum therapeutic dose, initially induces lesions in stomach pylorus and proximal duodenum but almost no effects were noted when duration of the drug administration was prolonged. Key Words: Indomethacin, Stomach, Duodenum.